Investigation of multi-bunching by generating multi-order fluorescence of NV center in diamond. Issue 8 (7th February 2018) - Tang, Haijun; Ahmed, Irfan; Puttapirat, Pargorn; Wu, Tianhao; lan, Yuwei; Zhang, Yanpeng; Li, Enling
Abstract : Fabricating electronics from solid-state quantum emitters is a promising strategy for the miniaturization and integration of electronic devices. Abstract : Fabricating electronics from solid-state quantum emitters is a promising strategy for the miniaturization and integration of electronic devices. However, the practical realization of solid-state quantum devices and circuits for signal transmission and processing at room temperature has remained challenging. Herein, we investigated the multi-bunching phenomenon by generating multi-order fluorescence from a pseudo-thermal source at room temperature using the nitrogen-vacancy (NV) center in diamond. We demonstrate the shift in time of multi-bunching by controlling the effect of dressing to realize logical gates and transistor switching operations. We also suggest the optimization of the time propagation delay (TPD) of the gate circuit by changing the boxcar gate position.